Design of a Web-Based Letter Submission Application at the Faculty of Science and Technology, University of Muhammadiyah Sidoarjo - Fahmi Anggara Santosa; Mochamad Alfan Rosid (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this research is to design a website for the submission of a cover letter which is intended to facilitate the making of a cover letter for students of the Faculty of Science and Technology, University of Muhammadiyah Sidoarjo. The method used in building this system is the waterfall method which starts from designing a system to make it easier to build the system and then collects data using observations to the administration of the faculty of science and technology in the form of letters that are often requested by students. The results of this system show that the system is able to run well, students can print letters that have been validated by the faculty admin, and letter files can be stored neatly in the faculty database. From the explanation above, the researcher concludes that this system can help students and admins in processing the submission of cover letters.